The Effect of Coffee Canopy Pruning and Fertilization on Coffee Growth and Soil Physical Properties - Rohani, Rosesita Tri Suci; Prayogo, Cahyo; Suprayogo, Didik; Wicaksono, Kurniawan Sigit (Green Engineering Society, 2024)
Arabica coffee is primarily cultivated in agroforestry systems in Indonesia, but limited local knowledge and technology adoption hinder its productivity due to insufficient practices in coffee pruning management. This study aims to analyze variations in coffee canopy pruning (Pruning+Bending) management and the impact on plant growth and soil physical characteristics.. The experiment employed a split-plot experimental design and utilized the Fisher test (5%) to assess the treatment effects. The primary plot focused on coffee canopy pruning using two management options: (1) Pruning (PR) and (2) Bending (BN). The subplots included various types and doses of fertilizer treatments: (1) Control (F0), (2) Chicken manure (F1), (3) Chicken manure+NPK fertilizer (F2), and (4) NPK fertilizer (F3). Each experimental plot covered an area of 20x20 m and contained 50 coffee plants. Bending techniques represent alternative pruning methods, and, in general, they have a significant impact on improving several coffee parameters compared to total pruning. Regarding the soil’s physical properties, the bending technique exhibited a higher infiltration rate than pruning. The management approach of Bending+Chicken manure: NPK fertilizer (BNF2) enhanced various coffee parameters, resulting in an increased stem diameter of 4.79 cm, new shoot length of 471.20 cm, and chlorophyll content of 6.83 mg/g. Furthermore, this treatment increased soil organic carbon content by 7.51% and reduced bulk density to 0.58 g/cm. In conclusion, the bending technique wasproven to be more advantageous than pruning, especially when combined with chicken manure and NPK fertilizer for enhancing coffee management among farmers.